2023
DOI: 10.1037/neu0000846
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic usefulness of experimental memory tasks for detecting subjective cognitive decline: Preliminary results in an Italian sample.

Abstract: Objective: Subjective cognitive decline (SCD) was recently proposed as an early risk factor for future mild cognitive impairment and Alzheimer’s disease (AD). In this study, we investigated the sensitivity of novel neuropsychological testing paradigms (which have been proposed as potentially challenging tools for the identification of preclinical AD) in capturing the subtle cognitive changes leading to SCD but not objectively detected by traditional tests. Method: The performances of 18 patients with SCD and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In those tasks, the lower performance level of the participants with SCD was not attributable to differences among the groups in terms of education level or depressive symptoms. These results are in line with studies indicating that tasks with a high cognitive processing load may be helpful for detecting impairment in SCD [ 20 , 23 , 24 , 25 , 26 , 27 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In those tasks, the lower performance level of the participants with SCD was not attributable to differences among the groups in terms of education level or depressive symptoms. These results are in line with studies indicating that tasks with a high cognitive processing load may be helpful for detecting impairment in SCD [ 20 , 23 , 24 , 25 , 26 , 27 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…Based on the findings of a six-year longitudinal study, Brailean et al argued that a decrease in subjective memory performance that cannot be explained by depressive symptoms may be detected by self-reported memory complaints [ 19 ]. Meanwhile, a recent study of a small group of individuals with SCD revealed an association between performance on demanding cognitive tasks and self-perceived memory functioning [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat different results were reported by De Simone et al (2022) in a study that investigated the diagnostic accuracy of a number of tests (including the FNAME test used by Flores-Vázquez et al, 2022) in distinguishing clinically diagnosed SCD participants from healthy controls. They found that the face-name test and a test assessing short-term pattern separation significantly discriminated between the two groups with good overall accuracy and that they were significantly associated with self-perceived memory functioning.…”
Section: Episodic Memorymentioning
confidence: 78%
“…These deficits could play a role in the progression to MCI. Moreover, it could be possible that new, more demanding tests might exhibit higher sensitivity for SCD [24]. However, depending on the cutoff, even standard neuropsychological tests may show interesting results.…”
Section: Who: Subjective Cognitive Declinementioning
confidence: 99%